'I forget to do pressure relief': Personal factors influencing the prevention of secondary health conditions in people with spinal cord injury, South Africa - Sonti Pilusa; Hellen Myezwa; Joanne Potterton (AOSIS, 2021)
Background: Across the lifespan, people with spinal cord injury (SCI) may experience preventable secondary health conditions (SHCs) such as pressures sores, muscle spasms and urinary tract infections (UTIs). Some factors influencing prevention of SHCs include social support, poor access to care and the prevention style of individuals. There is limited research on these factors. Objective: To explore personal factors influencing the prevention of SHCs in people with SCI. Method: An explorative qualitative study included participants recruited in an outpatient department at a rehabilitation hospital. Semi-structured interviews were conducted with patients with SCI. Interviews were transcribed verbatim. Data analysis was conducted using content analysis. Results: Seventeen individuals with SCI were interviewed. From the interview analysis, six personal factors were identified, namely, socio-economic status; mental well-being (forgetfulness, beliefs, attitude); lack of knowledge of SHCs and prevention; lifestyle choices and practising prevention care; patient activation (self-management, problem-solving, resilience, self-awareness, help-seeking behaviour) and owning an appropriate assistive device. Conclusion: Socio-economic status, mental well-being, knowledge of SHCs and prevention care, behaviour patterns, patient activation and owning an appropriate assistive device can influence prevention of SHCs. To enhance patient-oriented care, a model of care for people with SCI should consider these factors when developing prevention strategies. Future research could look into identifying environmental factors that influence the prevention of SHCs in people with SCI. Clinical implications: Tailored prevention strategies need to be developed, health professionals must ask patients about individual factors that may be barriers or facilitators to preventing secondary health conditions.